Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan UKMB (Usaha Mikro, Kecil Dan Menengah) Sektor Makanan Di Kota Denpasar - Bakti, Erlangga Mahardika; Saskara, Ida Ayu Nyoman (Jurnal Ilmiah Wahana Pendidikan, 2025)
The reason of this think about is to analyze the impact of e-commerce get to, commerce capital, and labor on the salary of culinary MSMEs in Denpasar City. The inspecting strategy utilized coincidental relative inspecting, coming about in a test measure of 80. From the conducted inquire about, the taking after comes about were gotten:To begin with, the e-commerce get to variable incorporates a positive and critical impact on income, demonstrating that higher item promoting on online deals stages leads to higher income levels. Moment, the commerce capital variable includes a positive and noteworthy impact on pay, inferring that entrepreneurs' income will increment in case they set out to extend the amount of types and merchandise exchanged, with the foremost influential factor being an increment in trade capital. Third, the labor variable contains a positive and critical impact on wage, meaning that an increment within the number of specialists comes about in higher efficiency and salary.